Measuring and analyzing the impact of banking services on supporting the tourism sector in the Kurdistan Region – Iraq - Mahmoud, Assy.L. Bashdar Nayef Mahmoud (Sulaimani Journal for Humanities, 2026)
This research investigates the role of banking sector in supporting the tourism sector in Kurdistan Region of Iraq. The first purpose of the study is to determine the possibility and ability of private banking sector in the Kurdistan Region to present the provide credit and online banking services to the tourism sector. One more goal of the research is studying and testing the impact of credit and online banking services in the development of the tourism sector to reach advanced stages compared to the revenues of hotels and tourism sector complexes in other countries. The results indicated that the Kurdistan Region has all the elements of tourism such as natural and human, might be Considering it as a safe and successful place for tourism investment and development. There is a huge capital investment in the tourism sector in Kurdistan Region; however, bank financing and loans for these investments are low compared to the size of those investments. To conclude, the consequences of statistical analysis show that increasing bank credit and electronic banking services have a multiplier effect on tourism revenues and increasing the number of resorts and hotels in the Kurdistan Region.
Keywords: credit; online services; tourism investment; tourism components